There's nothing plain about projection radiography! A discussion paper. Issue 4 (November 2021) - Mussmann, B.R.; Hardy, M.; Jensen, J.
Abstract: Objectives: Unlike the technological advances in cross-sectional imaging, the adoption of CR and DR has been relatively overlooked in terms of the additional radiographer skills and competences required for optimal practice. Furthermore, projection radiography is often referred to as basic, plain or other words suggesting simplicity or entry-level skill requirements. Radiographers' professional identity is connected with the discourse expressed via the language used in daily practice and consequently, if the perception of projection radiography is regarded as simple practice not requiring much reflection or complex decision-making, apathy and carelessness may arise. The purpose of this narrative review was to raise projection radiography from its longstanding lowly place and re-position it as a specialist imaging field. Key findings: Danish pre-registration radiography curricula contain little mention of projection radiography and a low proportion (n = 17/144; 11.8%) of Danish radiography students chose to focus on projection radiography within publicly available BSc. theses between 2016 and 2020 as compared to topics related to CT and MRI (n = 60/144; 41.7%). Conclusion: By changing how we as the profession perceive the role and position of projection radiography, we can start to rebuild its lost prestige and demand a greater, more detailed and clinically relevant educational offering from academic partners. For this to commence, the language and terminology we use to describe ourselves and tasks undertaken must reflect the complexity of the profession. Implications for practice: Regardless of imaging modality, every patient should be assured that a radiographer with expertise in acquiring images of diagnostic quality undertakes their examination. Reclaiming the prestige of projection radiography may lead students and radiographers to recognize projection radiography as a demanding specialist field for the benefit of the patients.